The time-spatial dimension of eurozone banking systemic risk - Matteo Foglia; Eliana Angelini (Risks, 2019)
In this paper, we measure the systemic risk with a novel methodology, based on a 'spatial-temporal' approach. We propose a new bank systemic risk measure to consider the two components of systemic risk: cross-sectional and time dimension. The aim is to highlight the 'time-space dynamics' of contagion, i.e., if the CDS spread of bank i depends on the CDS spread of other banks. To do this, we use an advanced spatial econometrics design with a time-varying spatial dependence that can be interpreted as an index of the degree of cross-sectional spillovers. The findings highlight that the Eurozone banks have strong spatial dependence in the evolution of CDS spread, namely the contagion effect is present and persistent. Moreover, we analyse the role of the European Central Bank in managing contagion risk. We find that monetary policy has been effective in reducing systemic risk. However, the results show that systemic risk does not imply a policy intervention, highlighting how financial stability policy is not yet an objective.
Keywords: 330; bank risk-taking; macroprudential policy; spatial contagion; systemic risk measure